Efek Antikariogenik Ekstrak Daun Beluntas (Pluchea indica) sebagai Penghambat Pertumbuhan Streptococcus Mutans penyebab Karies Gigi - Nungki Fatimatuzzahra; Nourmalita Safitri Ningsih; Feny Feny; Adam Darsono; Siti Isrina Oktavia Salasia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Anti-plaque agents are known to reduce the formation of dental biofilms such as fluoride and chlorhexidine. However, excessive use of fluoride causes fluorosis and chlorhexidine side effects caused genotoxic. Pluchea indica L is one of the abundance of tropical herbs in the Asia-Pacific reported to have antiinflammatoryproperties and reduces the incidence of gastric necrosis, antinociception, neutralizing toxic venom, antioxidant, antiulcerative, hepatoprotective, antimoeba and broad-spectrum antimicrobial. This study examinesthe effectiveness anticariogenic Pluchea indica leaf extract in inhibiting the growth of Streptococcus mutans causing dental caries in vitro. Determination of Minimum Inhibitoric Concentration (MIC) on Pluchea indica leafextract is by diffusion test on the growth of Streptococcus mutans by Kirby Bauer Test. S. mutans concentration Mc Farland 0.5 standard (108 CFU ml-1) were inoculated in media Müller-Hinton agar (MHA). Paper diskcontaining Pluchea indica leaf extract at each concentration of 10%, 20%, 30%, 40%, 50%, 60%, and 70% were placed in an agar medium inoculated bacteria then incubated at 37°C on condition microaerophilia using candlejar. Determination of significance various Pluchea indica leaf extract concentration using one-way ANOVA test. The result of the diffusion method showed Pluchea indica leaf extract at a minimum concentration of 10% beenable to establish inhibited zone of Streptococcus mutans growth in MHA media. By one-way ANOVA test to various concentrations of extracts using Microsoft Excel 2007 have been obtained with F=4.85, Fcrit = 2.85 andP-value = 0.0071. Based on this research, it was concluded that Inhibitoric Minimum Concentration Pluchea indica leaf extract is capable of effective concentration of 10% and it has a significant (P-value< 0,05) of variousconcentration.